LHC tau-pair production constraints on $a_τ$ and $d_τ$ - Ulrich Haisch, Luc Schnell, Joachim Weiss (SciPost Physics, 2024)
We point out that relevant constraints on the anomalous magnetic ($a_τ$) and electric ($d_τ$) moment of the tau lepton can be derived from tau-pair production measurements performed at the LHC. Our conclusion is based on the observation that the leading relative deviations from the Standard Model prediction for $pp → τ^+ τ^-$ due to $a_τ$ and $d_τ$ are enhanced at high energies. Less precise measurements at hadron colliders can therefore offer the same or better sensitivity to new physics with respect to high-precision low-energy measurements performed at lepton machines. We derive bounds on $a_τ$ and $d_τ$ using the full LHC Run II data set on tau-pair production and compare our findings with the current best limits on the tau anomalous moments.